Implementasi Sistem Informasi Akuntansi Menggunakan Zahir Accounting pada PT. Bangunan Jaya Perkasa Tangerang - Ahmad Yani; Yuslin; Yuslin Yuslin (LPPM Universitas Bina Sarana Informatika, 2022)
Abstract – Accounting Information System is a system that processes company data into financial information (financial reports). Financial information of a company will describe how the condition of a company during a certain period. Based on the resulting financial information, the company's policy is determined by the company's management. Of course, the company's management in making a policy must be based on quality financial information so that the policies made are not wrong. So far, the company PT.Bangunan Jaya Perkasa has been processing company data to produce financial information that is still manual. This is of course very problematic in terms of accuracy and accuracy as well as the speed of financial information needed by the management. Zahir Accounting is one of the application software in the accounting information system that can be used to process company transaction data to produce quality financial information needed by stakeholders in managing the company. The method used in this study is a qualitative method which emphasizes the observation of the phenomenon of case studies of accounting data processing and examines the substance of the meaning of the phenomenon. The purpose of this study is to provide the right solution for the problems faced by the management of the company PT.Bangunan Jaya Perkasa Tangerang in processing company transaction data to produce financial information that is fast, accurate, and relevant. With this research, it is hoped that it can be used as a repertoire of references for further research in the field of similar research. Keywords: Accounting Information System, Financial Report